Development of computer based two-tier multiple choice diagnostic test to identify misconceptions on chemical bonding. Issue 4 (February 2019) - Utami, G R; Firman, H; Nahadi, N
Abstract: This research aims to find a computer-based two-tier multiple choice diagnostic test of student misconceptions on chemical bonding. The process of developing diagnostic test is conducted by: (1) analyzing student misconceptions on chemical bonding including analysis of the literature of previous journals and misconception books, (2) identification of concept targets, (3) analysis of student misconception through essay question given, and (4) the diagnostic questions compilation of a computer-based two-tier multiple choice misconception analysis result from related reference and essay test which given to student got ten general misconceptions. There are four materials which are ionic bonds, covalent bonds, metal bonds and coordination bonds. A computer-based of two-tier multiple choice diagnostic test on chemical bonding will be tested the affectivity by tested, misconceptions identification from feedback and re-tested again.